Bazar sebagai Alternative Menumbuhkan Jiwa Wirausaha Berbasis Kearifan Lokal Mahasiswa - Muhamad Yusuf; Rini Syevyilni Wisda; Yelni Erniyati (Yayasan Kajian Riset Dan Pengembangan Radisi, 2026)
Entrepreneurship learning in higher education is one way to instill entrepreneurial values ​​and spirit for students as one way to face the competition of the world of work. Cultivating the entrepreneurial spirit with applied activities from various theories learned in class through bazaar activities based on local wisdom. The bazaar is carried out by developing local products, local potential, consisting of natural products that have utility value, sales value but are often forgotten. This bazaar process is carried out through several stages starting from planning, implementation, evaluation. The bazaar process is carried out through activities planning bazaar members, planning products with local wisdom value that will be produced innovatively, marketed at bazaar activities, implementation activities, including the bazaar activity process, starting from marketing products to serving consumers and evaluation activities reviewing and measuring the implementation of bazaar activities. Bazaar activities are able to create a meaningful learning process such as being able to build values, entrepreneurial spirit including, the value of daring to start, daring to find ideas, designing products, courage to manage risks, creativity, innovation, responsibility in students.